2003
DOI: 10.1177/073953290302400404
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Large Newspapers Studies Information Practices

Abstract: A survey of daily newspapers with more than 100,000 circulation provides general markers for six areas of information practice: access, training, quality control, archiving, revenue and alerts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Digital photography also permitted the concerned authorities to present the required evidence in the court against the crimes. Past studies also confirmed that digital photography, digital images, videos, and others ways of digital communication are been prominently adopted legally in the courts [6,8,25,27]. Even courts and police stations have begun using software programs that allow them to retrieve digital images from the computer, modify them, and store the images or crime scenes for future references.…”
Section: Advantages Of Digital Photographymentioning
confidence: 96%
See 3 more Smart Citations
“…Digital photography also permitted the concerned authorities to present the required evidence in the court against the crimes. Past studies also confirmed that digital photography, digital images, videos, and others ways of digital communication are been prominently adopted legally in the courts [6,8,25,27]. Even courts and police stations have begun using software programs that allow them to retrieve digital images from the computer, modify them, and store the images or crime scenes for future references.…”
Section: Advantages Of Digital Photographymentioning
confidence: 96%
“…Even courts and police stations have begun using software programs that allow them to retrieve digital images from computer, modify them, and store the images or crime scenes for future references. By doing so, legal departments can have a database along with them, unlike the traditional legal system [4,6,9,10]. Police departments also began using digital photography to transmit and store digital images, which could be crucial for the cases registered.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…A news organization that embraces the web and other forms of online information-gathering can overcome these barriers. (Garrison, 2001, p. 234) Following up with Garrison's extensive work, Hansen, Paul and Neibergall (2003) surveyed newsrooms and obtained a baseline on six critical areas of information practices: access, training, quality, archiving, revenue, and alerts. They found out that, aside from access, which had been improved by online services and libraries, newsrooms still need to work on the remaining five, especially revenue and alerts.…”
Section: Technology In the Newsroom And A New Type Of Readermentioning
confidence: 99%